A Parallelization Scheme for New DPD-B Thermostats. (12th November 2013) - Moga, S. A.; Dragoi, G.; Hadar, A.; Goga, N.
Abstract : This paper presents the MPI parallelization of a new algorithm—DPD-B thermostat—for molecular dynamics simulations. The presented results are using Martini Coarse Grained Water System. It should be taken into account that molecular dynamics simulations are time consuming. In some cases the running time varies from days to weeks and even months. Therefore, parallelization is one solution for reducing the execution time. The paper describes the new algorithm, the main characteristics of the MPI parallelization of the new algorithm, and the simulation performances.